A new species of Eucosma Hübner and two new species of Cydia Hübner (Lepidoptera: Tortricidae) from the United States - Brown, Richard L.; Jaeger, Christi (Zootaxa, 2014)
Three new species of Olethreutinae (Lepidoptera: Tortricidae) from the United States are described and illustrated. Eucosma paregoria Brown, n. sp., is associated with prairies and glades, primarily in midwestern U.S. Cydia marita Brown, n. sp., is common in southeastern U.S., ranging from Texas to Florida and north along the eastern seaboard to Virginia. Cydia timara Brown, n. sp., occurs in the southwestern U.S. (Arizona and New Mexico). Both species of Cydia are associated with habitats that support Pinus species, the probable larval hosts.